The boy in the dress - Walliams, David; Blake, Quentin (London HarperCollins Children's Books, 2009)
Dennis, who lives in a boring down in a boring house and has a passion for soccer - and fashion. When his friend Lisa discovers his stash of Vogue magazines and convinces him to wear a dress to school, trouble begins. A compelling, unusual story offers black and white drawings by Quentin Blake throughout